Toward a multiracial feminist framework for understanding females' gang involvement. Issue 3 (3rd July 2017) - Peterson, Dana; Panfil, Vanessa R.
Abstract: Despite growing interest in the gang involvement of girls and young women, tools with which to understand the experiences leading them to gangs remain fragmented. This article draws from existing gang theories and research on gendered pathways to illustrate the utility of a unified conceptual framework, particularly, one grounded in multiracial feminism. We explain what the primary components of such an integrated, life-course framework should be. Specifically, our framework attempts to account for multi-level influences: macro-level interlocking systems of inequality such as racialization and heteronormativity; interpersonal interactions in meso-level proximal spheres such as neighborhoods, families, schools, and peer groups; and micro-level processes of situated action, such as identity negotiation and agency within the context of constrained choice. We argue that our proposed conceptual framework will allow for more nuanced and complex understandings of females' gang involvement.